Root Coverage Associated with Acellular Dermal Matrix and L-Prf in Bilateral Unitary Gingival Recessions – Case Report - Damião, Anne Carolinne Neves; Santos, Geovana Feitosa dos; de Souza Fonseca, Ricardo Roberto; de Almeida Machado, Luiz Fernando; de Menezes, Silvio Augusto Fernandes; Pessoa de Oliveira, Paula Gabriela Faciola (The Journal of Dentists, 2020)
Gingival recession can be defined as the displacement of the marginal tissue apical to the cemento-enamel junction exposing the root surface of teeth. To restore the displaced tissue, grafts are used mainly to modify the periodontal biotype and reconstruct the gingival tissue and among graft types we mention autogenous, xenogenous and allogeneic. This paper aims to report a case of bilateral root coverage using acellular dermal matrix (ADM) graft and platelet-rich fibrin (L-PRF) membrane. Female patient, 27 years old, non-smoker and no previous medical conditions attended to a college dental clinic in northern Brazil with the main complaint of dental hypersensitivity. On intraoral exam it was observed gingival recessions stage II type 1 in teeth 13 and 23 due to orthodontic treatment. After preoperative exams and oral cavity adequacy, the recommended treatment was root coverage by Zucchelli & De Sanctis technique with autogenous graft. However due to the hard palate thin thickness and the patient’s refusal to have a second postoperative area xenogenous and allogeneic were used. During the surgical procedure a coronally advanced flap without relaxing incisions were made and associated with L-PRF membrane in tooth 23 and ADM graft in tooth 13, then the coronal flap was fixed with sutures. We conclude that the use of L-PRF and ADM are viable techniques and with excellent predictability of success; both improved the range of keratinized mucosa and promoted clinical attachment level (CAL) increase.